2011
DOI: 10.1590/s0034-737x2011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Respostas fisiológicas e desempenho produtivo de ovinos em pasto suplementados com diferentes fontes proteicas

Abstract: Physiological responses and performance of sheep on pasture supplemented with different protein sourcesThis study was carried out to evaluate the influence of climatic factors on performance and physiological responses of sheep fed on different protein supplements in grazing Tifton 85 (Cynodon spp.) irrigated in conditions of Brazilian semiarid climate. A total of 28 male Santa Ines x SPRD (undefined breed), castrated lambs, with initial weight of 28 kg, received three different sources of protein in the suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…The enviromental temperature in semi-arid conditions, as expected and reported by several authors (Santos et al, 2005(Santos et al, , 2007Silva et al, 2012Silva et al, , 2013b, was higher (P<0.05) in the afternoon, probably due to the higher incidence and intensity of sunlight at this time, showing a temperature range of 7.8 °C. These values, when compared to the established as thermal comfort zone for adult sheep, where according to Baêta and Souza (2010), is in the range 15-30 °C, and the critical temperature above 35 °C, which characterizes a situation of thermal stress to the driving conditions of the experiment, as is confirm by Oliveira et al (2011).…”
Section: Resultssupporting
confidence: 72%
“…The enviromental temperature in semi-arid conditions, as expected and reported by several authors (Santos et al, 2005(Santos et al, , 2007Silva et al, 2012Silva et al, , 2013b, was higher (P<0.05) in the afternoon, probably due to the higher incidence and intensity of sunlight at this time, showing a temperature range of 7.8 °C. These values, when compared to the established as thermal comfort zone for adult sheep, where according to Baêta and Souza (2010), is in the range 15-30 °C, and the critical temperature above 35 °C, which characterizes a situation of thermal stress to the driving conditions of the experiment, as is confirm by Oliveira et al (2011).…”
Section: Resultssupporting
confidence: 72%
“…A irrigação pode ser acionada nos veranicos ou na estação seca, quando a precipitação pluvial é insuficiente para atender as necessidades de água das gramíneas. A forragem tropical, de forma isolada pode não conferir elevados ganhos de peso aos animais, especialmente àqueles de maior mérito genético que possuem maiores exigências nutricionais e, dessa forma, uma maneira de potencializar os ganhos individuais dos animais em pastejo é o uso da suplementação alimentar, a exemplo da suplementação com concentrado (SOUZA et al, 2010;OLIVEIRA et al, 2011).…”
Section: Introductionunclassified
“…This inference was made by observing longer grazing periods and because sheep prefer eating leaves (Table 3). Oliveira et al (2011) observed a decrease in forage consumption by sheep supplemented with different protein sources (urea and soybean and cottonseed meals), when compared with the pasture-fed animals; they reported that this occurred due to the substitution consumption of supplements for pasture. An increase in the daily grazing time of animals is a behavioral strategy for compensating reduction in nutrient consumption during limiting conditions in pastures with unfavorable structural and qualitative characteristics.…”
Section: Resultsmentioning
confidence: 99%